INTEGRASI NILAI-NILAI MULTIKULTURAL MELALUI PEMBELAJARAN IPS - Akib, Nirwana; Guntara, Fuad; Ahdar, Ahdar; Zurahmah, Zurahmah (Social Landscape Journal, 2025)
This study aims to determine how the integration of multicultural values through Social Studies (IPS) learning at SMP Negeri 4 Parepare. The approach used in this study is a qualitative approach with a descriptive research type. Informants in this study consisted of IPS teachers and students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that multicultural values such as tolerance, cooperation, and respect for diversity have been integrated into IPS learning both directly through teaching materials and indirectly through learning strategies and approaches used by teachers. Teachers actively prepare lesson plans that reflect these values and implement them through participatory learning methods such as discussions, case studies, and cultural projects. Students responded positively to this learning and showed changes in attitudes in everyday life, such as respecting differences, living in harmony, and participating in cross-cultural activities. This integration has been shown to contribute to the creation of a harmonious and inclusive learning climate in the school environment.